Effect of Magnet Position on Tipping and Bodily Tooth Movement in Magnetic Force-Driven Orthodontics - Yoshiki Ishida (Materials, 2020)
The goal of our study is to launch magnetic force-driven orthodontics. This continuous study investigated the influence of magnet position on tipping and bodily tooth movement, using 3D printing technology and digital analysis. Orthodontic typodont models (TMs) for space-closure were 3D printed to mimic maxillary central incisors. Nd-Fe-B magnets were placed in the middle third (Model-M), and the cervical third (Model-C), of the tooth. TMs, before and after movement, were digitally scanned and superimposed. The 3D digital coordinates (X, Y, and Z axes), and rotations (yaw, pitch, and roll) of the tooth crown and root, were calculated and compared between the two magnet position settings. Model-M showed higher rates of movement, but more rotation than Model-C (p < 0.01). The root apex of Model-M moved in the opposite direction of the crown (R = −0.29), indicating tipping movement. In contrast, the crown and root apex moved in the same direction (R = 0.56) in Model-C, indicating bodily movement. These patterns were confirmed in a typodont model of a moderate crowding case. The results validated that modifying the magnet position increased the amount of bodily tooth movement, and decreased rotation/tipping in an ex vivo setting.